Morphological evolution of lamellar forming polystyrene-block-poly(4-vinylpyridine) copolymers under solvent annealing. Issue 24 (31st May 2016) - Ghoshal, Tandra; Chaudhari, Atul; Cummins, Cian; Shaw, Matthew T.; Holmes, Justin D.; Morris, Michael A.
Abstract : In this work, we are reporting a simple and efficient method to form lamellar structures of symmetric polystyrene- block -poly(4-vinylpyridine) (PS- b -P4VP) copolymer thin films with vertically (to the surface plane) orientated lamellae using a solvent annealing approach. Abstract : In this work, we are reporting a very simple and efficient method to form lamellar structures of symmetric polystyrene- block -poly(4-vinylpyridine) (PS- b -P4VP) copolymer thin films with vertically (to the surface plane) orientated lamellae using a solvent annealing approach. The methodology does not require any brush chemistry to engineer a neutral surface and it is the block neutral nature of the film-solvent vapour interface that defines the orientation of the lamellae. The microphase separated structure of two different molecular weight lamellar forming PS- block -P4VP copolymers formed under solvent vapour annealing was monitored using atomic force microscopy (AFM) so as to understand the morphological changes of the films upon different solvent exposure. In particular, the morphology changes from micellar structures to well-defined microphase separated arrangements. The choice of solvent/s (single and dual solvent exposure) and the solvent annealing conditions (temperature, time etc. ) has important effects on structural transitions of the films and it was found that a block neutral solvent was required to realize vertically aligned P4VP lamellae. The results of the structural variation of the phase separated nanostructured films through the exposure to ethanol are also described.